ACEH ULEMA COUNCIL AND CONSUMER PROTECTION ROLES IN HALAL FOOD-BEVERAGE CERTIFICATION UNDER SHARIA ECONOMIC LAW - Saprina, Laily; Soraya Devi; Misran (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This article aims to analyse the role of the Aceh Ulama Council (MPU) in the implementation of halal certification for food and beverage products, and its relation to the protection of Muslim consumers, from the perspective of Islamic economic law. The research method used is qualitative, with a juridical-empirical approach, drawing on literature studies, related regulations, and interviews with consumers and the Aceh MPU LPPOM. The results of the study show that although Aceh Qanun No. 8 of 2016 on the Halal Product Guarantee System has been in effect since 2016, its implementation remains suboptimal. This is evident in the large number of food and beverage products, including imported products, that circulate without halal labels. LPPOM MPU Aceh plays a role in the halal certification process through administrative checks, laboratory testing, and certificate issuance. Still, its implementation is hampered by low consumer awareness, limited business compliance, and a lack of coordination among relevant institutions. From a Sharia economic law perspective, the existence of halal certification is not only a form of protection for Muslim consumers but also the implementation of the halalan thayyiban principle to safeguard the interests of the people and create a sense of security in the consumption of everyday products. Therefore, strengthening regulations, increasing the capacity of business actors, and continuously educating the public are essential steps to raise awareness of the importance of halal products and achieve the objectives of Islamic economic law optimally.